The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1098/rspb.2016.1125
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trophic level response to extreme metal contamination from gold mining in a subarctic lake

Abstract: Giant Mine, located in the city of Yellowknife (Northwest Territories, Canada), is a dramatic example of subarctic legacy contamination from mining activities, with remediation costs projected to exceed $1 billion. Operational between 1948 and 2004, gold extraction at Giant Mine released large quantities of arsenic and metals from the roasting of arsenopyrite ore. We examined the long-term ecological effects of roaster emissions on Pocket Lake, a small lake at the edge of the Giant Mine lease boundary, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 63 publications
(84 reference statements)
3
89
0
Order By: Relevance
“…Our early findings showed that the onset of As contamination in a naturally fishless lake in the 1950s initially favored Daphnia, known from laboratory studies to be relatively tolerant of As, until extreme As contamination eventually led to the functional extirpation of all Cladocera in the lake by the 1970s (Thienpont et al 2016). No long-term monitoring records are available for Yellowknife lakes impacted by Au mining activities, but even if records were available, they likely would not have been of sufficient duration to capture the appearance and increasing abundance of Daphnia following As contamination, only their demise.…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 80%
See 1 more Smart Citation
“…Our early findings showed that the onset of As contamination in a naturally fishless lake in the 1950s initially favored Daphnia, known from laboratory studies to be relatively tolerant of As, until extreme As contamination eventually led to the functional extirpation of all Cladocera in the lake by the 1970s (Thienpont et al 2016). No long-term monitoring records are available for Yellowknife lakes impacted by Au mining activities, but even if records were available, they likely would not have been of sufficient duration to capture the appearance and increasing abundance of Daphnia following As contamination, only their demise.…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 80%
“…Species fossilized remains include many commonly used model organisms in ecotoxicology, especially Daphnia (zooplankton) and Chironomidae (aquatic insects) larvae. This historical archive of ecotoxicological information has traditionally been underutilized, but "paleo-ecotoxicology" is gaining prominence as a valuable tool to examine the ecological consequences of long-term exposure to environmental contaminants (e.g., Thienpont et al 2016). We believe that improved collaboration and flow of information among paleolimnologists and ecotoxicologists will lead to rapid advances in our understanding of the long-term consequences of exposure to aquatic contaminants.…”
mentioning
confidence: 99%
“…We are applying this approach in an ongoing multidisciplinary project to investigate the legacy impacts of As contamination from historic Au mining activities in subarctic lakes near Yellowknife, Northwest Territories, Canada. Our early findings showed that the onset of As contamination in a naturally fishless lake in the 1950s initially favored Daphnia, known from laboratory studies to be relatively tolerant of As, until extreme As contamination eventually led to the functional extirpation of all Cladocera in the lake by the 1970s (Thienpont et al 2016). No long-term monitoring records are available for Yellowknife lakes impacted by Au mining activities, but even if records were available, they likely would not have been of sufficient duration to capture the appearance and increasing abundance of Daphnia following As contamination, only their demise.…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 80%
“…We are applying this approach in an ongoing multidisciplinary project to investigate the legacy impacts of As contamination from historic Au mining activities in subarctic lakes near Yellowknife, Northwest Territories, Canada. Our early findings showed that the onset of As contamination in a naturally fishless lake in the 1950s initially favored Daphnia , known from laboratory studies to be relatively tolerant of As, until extreme As contamination eventually led to the functional extirpation of all Cladocera in the lake by the 1970s (Thienpont et al ). No long‐term monitoring records are available for Yellowknife lakes impacted by Au mining activities, but even if records were available, they likely would not have been of sufficient duration to capture the appearance and increasing abundance of Daphnia following As contamination, only their demise.…”
mentioning
confidence: 94%
“…Species fossilized remains include many commonly used model organisms in ecotoxicology, especially Daphnia (zooplankton) and Chironomidae (aquatic insects) larvae. This historical archive of ecotoxicological information has traditionally been underutilized, but “paleo‐ecotoxicology” is gaining prominence as a valuable tool to examine the ecological consequences of long‐term exposure to environmental contaminants (e.g., Thienpont et al ). We believe that improved collaboration and flow of information among paleolimnologists and ecotoxicologists will lead to rapid advances in our understanding of the long‐term consequences of exposure to aquatic contaminants.…”
mentioning
confidence: 99%